AI adoption among adolescents in education: extending the UTAUT2 with psychological and contextual factors - Caffaratti, Luca Ballestra; Longobardi, Claudio; Badenes-Ribera, Laura; Marengo, Davide (Frontiers in Artificial Intelligence, 2025)
IntroductionThis correlational study investigates the psychological and contextual factors associated with the adoption of artificial intelligence (AI) technologies among Italian high school students. Building on the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), the study extends the model by incorporating Problematic Internet Use (PIU) and Attitudes Toward AI (ATAI) to better account for habitual AI use and behavioural intentions.MethodA sample of 933 students (Mage = 16.20, SDage = 1.29, 54.98% female) completed a survey assessing key UTAUT2 dimensions, psychological traits, and usage patterns of AI tools in educational contexts. Confirmatory factor analysis (CFA) was used to evaluate the functioning of the adapted UTAUT2. Multiple regression was used to investigate factors predicting habit formation and behavioural intention related to AI use.ResultsConfirmatory factor analysis supported the structural validity of the adapted UTAUT2 model. Multiple regression analyses revealed that Performance Expectancy, Social Influence, Hedonic Motivation, and Schoolwork-related AI use were significant predictors of both habit and behavioural intention. PIU showed a robust association with habitual use, suggesting a spillover effect from compulsive Internet behavior to AI engagement. ATAI was associated only with behavioural intention, indicating its role in initial adoption rather than sustained use. Demographic and contextual factors (e.g., school type, citizenship) showed additional effects.DiscussionThese findings contribute to a more comprehensive understanding of adolescent AI engagement by highlighting the role of compulsive tendencies and motivational beliefs. The study underscores the importance of designing inclusive, age-appropriate interventions to promote balanced and informed AI use in educational settings.